Does Allowing Track 2 MAiD Harm Disabled People? - Abernethy, Nicholas (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
In 2021, in response to the Superior Court of Quebec’s decision in Truchon v. Canada, the Canadian Parliament amended the Criminal Code to allow Medical Assistance in Dying (MAiD) for some people who don’t have a “reasonably foreseeable natural death.” Debate rages over this amendment. In particular, some academics and activists argue that it should be repealed because it discriminates against disabled people. In 2024, these arguments appeared in a Canadian court proceeding; two disabled individuals and four disability rights organizations filed a lawsuit in the Ontario Superior Court of Justice, challenging the amendment. In this paper, I critically analyze the harm-centric arguments in the applicants’ notice of application (which crystallizes the broader opposition to the amendment). In doing so, I draw on analysis from both sides of the ethical debate over the amendment. Ultimately, I conclude that the applicants’ arguments — and those from other opponents of the amendment — don’t succeed. Some of my recurring objections include that the alleged harmful effects of the amendment are either 1) harmful only if the applicants’ dubious ethical assumptions are true, 2) not attributable to the amendment, or 3) nonexistent, negligible, or unlikely. In defence of the amendment, I discuss how it respects people’s autonomy and avoids instrumentalization.